THE TRANSLATION OF TRANSITIVITY PROCESS IN A SHORT STORY OF THE YELLOW FACE IN THE BOOK OF THE MEMOIRS OF SHERLOCK HOLMES - Halimatus Sa'adah; M. R. Nababan; Riyadi Santosa (International Conference on Social and Islamic Studies, 2021)
Short story is a narrative text that describes an experience or event of an actor in a sequence of time. The phenomenon of experience is related to the study of SFL, namely transitivity. Transitivity is a grammatical that explains the meaning of experience into a type of processes. This study aims to analyze the translation of narrative text, that is a short story. The aims of this research are a) to identify the type of transitivity process of narrative text from the source language and target language, b) to find out the transitivity process translation technique applied by the translator in translating the narrative text. The research method used is descriptive qualitative with a functional systemic linguistic approach. The transitivity theory is based on Halliday's theory (2014). The data was obtained through content analysis and FGD (focus group discussion). The results showed that there were 48 clauses obtained by determining the generic structure of the narrative text. There were 6 types of transitivity process in the short story of The Yellow Face, such as material process, mental process, attributive relational process, verbal process, existential process, and verbal behavior process. Meanwhile, the translation techniques applied to translate the transitivity process are establish equivalent (77%), modulation (14,58%), explicitation (6,25%), and paraphrase (2,08%).